2010
DOI: 10.1016/j.biortech.2010.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of bioemulsifier-producing yeasts isolated from effluents of a dairy industry

Abstract: New bioemulsifier-producing yeasts were isolated from the biological wastewater treatment plant of a dairy industry. Of the 31 bioemulsifier-producing strains, 12 showed emulsifying activity after 2months of incubation, with E(24) values ranging from 7% to 78%. However, only Trichosporon loubieri CLV20, Geotrichum sp. CLOA40, and T. montevideense CLOA70 exhibited high emulsion-stabilizing capacity, with E(24) values of 78%, 67%, and 66%, respectively. These isolates were shown to induce a strong emulsion stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 33 publications
4
49
0
3
Order By: Relevance
“…It was recently reported that yeast strains of the genus Trichosporon and Geotrichum have the ability to produce bioemulsifiers that are able to emulsify toluene. These SACs are produced in culture medium supplemented with sunflower oil, and the bioemulsifier compounds contain (9Z,12Z)-octadeca-9,12-dienoic acid and mannose, galactose, xylose and arabinose monosaccharides [12]. …”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that yeast strains of the genus Trichosporon and Geotrichum have the ability to produce bioemulsifiers that are able to emulsify toluene. These SACs are produced in culture medium supplemented with sunflower oil, and the bioemulsifier compounds contain (9Z,12Z)-octadeca-9,12-dienoic acid and mannose, galactose, xylose and arabinose monosaccharides [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The compound 2, (2E)-1-(4´-hydroxy-2´,6´-dimethoxy-3´,5´-dimethylphenyl)-3-phenylprop-2-en-1-one, showed similar structure to 1, seems to be an unedited substance. The compounds 3-4, isolated as pale yellow solids, were elucidated by means of NMR data, hydrolysis, peracetylation and GC/MS analysis (Cota et al, 2008;Monteiro et al,2009;Monteiro et al, 2010). It was possible to confirm the identity of the sugar moiety as rhamnose for 3 (Figure 1) and arabinose for 4 (Figure 2).…”
Section: Cytotoxicity Assays With Human Cancer Cell Lineagesmentioning
confidence: 96%
“…Bioemulsifiers are able to stabilize emulsions by increasing their kinetic stability and this property has increased their usefulness in the cosmetics, food, pharmaceutical and petroleum industries. Reports have shown that the efficient emulsifying activity of bioemulsifiers is a function of their chemical composition (Calvo et al, 2009;Monteiro et al, 2010). According to Willumsen and Karlson (1997), surface active biomolecules are categorized into surfactants and emulsifiers, while surfactants play the role of surface tension reduction, emulsifiers are involved in formation and stabilization of emulsions.…”
Section: The Physiological Roles Of Biosurfactants and Bioemulsifers mentioning
confidence: 99%
“…Halomonas eurihalina produces an exopolysaacharide (EPS) that acids and proteins produced by Klebsiella sp. On a general note bioemulsifiers have been associated with a number of potential applications including: remediation of oil polluted water and soil; enhanced oil recovery and clean-up of oil contaminated vessels and machineries; heavy metal removal (Monteiro et al, 2010;Zheng et al, 2012;Panjiar et al, 2014); formation of stable emulsions in food and cosmetics industries ; and therapeutic activities (antibacterial, antifungal, pesticidal and herbicidal agents) (Ahmed and Hassan, 2013). The physico-chemical properties of bioemulsifiers and biosurfactants are presented in Table 1.…”
Section: The Physiological Roles Of Biosurfactants and Bioemulsifers mentioning
confidence: 99%
See 1 more Smart Citation